ChemInform Abstract: An Efficient Isocyanide‐Based Three‐Component Diastereoselective Synthesis of Chromane‐3, 4‐dicarboxamides. Issue 11 (18th March 2014) - Imanieh, Hossein; Sarlak, Mansooreh; Amanpour, Tayebeh; Bazgir, Ayoob
Abstract Performing the reaction with aliphatic amines gives only complex mixtures of numerous products.